2020
DOI: 10.1021/acs.macromol.9b02512
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Hydrogen-Bonded Antioxidant Films of Linear Synthetic Polyphenols

Abstract: We report on the role of the chemical structure of polyphenol pendant groups in linear antioxidant polymers in their assembly and chain intermixing within layer-by-layer (LbL) films, as well as in the antioxidant performance of interfacial assemblies. When assembled with poly(ethylene oxide) (PEO) within hydrogen-bonded films, the antioxidant polymerspoly(3,4dihydroxybenzyl methacrylamide) (P2HMA) and poly(3,4,5-trihydroxybenzyl methacrylamide) (P3HMA)which contain catechol-and gallol-like moieties, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 73 publications
2
27
0
Order By: Relevance
“…Oxidized EGCG by tyrosinase can be coupled with primary amines on the glycol chitosan. However, upon completion of hydrogel formation, unconjugated or unreacted EGCGs may be retained within the hydrogel structure [ 31 , 32 ]. These EGCGs may be entrapped within a cross-linked hydrogel network and are prone to sustained release from the hydrogel (via diffusion).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidized EGCG by tyrosinase can be coupled with primary amines on the glycol chitosan. However, upon completion of hydrogel formation, unconjugated or unreacted EGCGs may be retained within the hydrogel structure [ 31 , 32 ]. These EGCGs may be entrapped within a cross-linked hydrogel network and are prone to sustained release from the hydrogel (via diffusion).…”
Section: Discussionmentioning
confidence: 99%
“…Ji et al [50] prepared ciprofloxacin/ polyallylamine hydrochloride/SiO 2 /polyallylamine hydrochloride (abbreviated as CIP/PAH/SiO 2 /PAH) multilayers on the surface of AZ31 Mg alloy by spin-spray LbL assembly. The presence of SiO 2 NPs not only improved the corrosion resistance of the substrate, but also endowed the coating with self-healing properties in which the particles can locate and effectively diffuse to the area of nanoscale cracks to repair the damaged regions [51]. The degradable graphene oxide (GO) is another optional assembly unit to improve corrosion resistance due to its high aspect ratio.…”
Section: Reviewmentioning
confidence: 99%
“…SCIENCE CHINA Materials functional films by this assembly technique has also been studied in many fields [51,59]. Nevertheless, there are few reports on preparing hydrogen bonding-driven LbLassembled coating on Mg alloys.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 We demonstrated that the structure of the polyphenol rings has a strong effect on the film growth regime, film internal structure, and the ability of these assemblies to scavenge radicals. 53 In this work, we aim to understand the underlying dynamics driving these behaviors. Using NR to track infusion of deuterated PEO chains into linear and exponential hydrogen-bonded LbL films, in situ ellipsometry to monitor kinetics of mass deposition during film construction, and AFM to track healing of tip-indented films upon exposure to water, we have uncovered differences in chain diffusivity between film components during film construction and correlate these with the film growth mode and the structure of the polyphenol ring in hydrogen-bonded linear polymers.…”
Section: ■ Introductionmentioning
confidence: 99%